Justice sociale et durabilité, la rencontre est-elle possible ? Portée politique de l’expérience vécue des injustices écologiques - Caroline Lejeune (VertigO)
Since the early 1990s, environmental justice movements have demonstrated that the environment is a source of injustice, adding to existing inequalities. Repair tools and regulatory and participatory procedures have been developed to provide responses to the victims of environmental inequalities. While these theoretical and practical approaches have contributed to recognizing this new form of injustice and putting the challenges of environmental justice on the political agenda. They nevertheless seem to be insufficient to deal with environmental irreversibilities. We will present the theoretical and practical limits of distributive justice in a finite world as presented by green political theory and ecocentric ethics. We will then be able to question the ontological and epistemic stakes that an ecological justice offers in a political thought. We will underline the contribution of the sensible and material relation to the nature to apprehend a justice in a finite world.